2016
DOI: 10.18632/oncotarget.13984
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelin-targeted immunotoxin RG7787 has synergistic anti-tumor activity when combined with taxanes

Abstract: Recombinant immunotoxins (RITs) are antibody-based therapeutics that carry a toxin payload. The RG7787 RIT targets the cancer antigen mesothelin to deliver a recombinantly-engineered, reduced immunogenicity variant of Pseudomonas exotoxin A (PE) to the cytosol where it inhibits protein synthesis. Here we demonstrate that maximal doses of RG7787 temporarily halt growth of pancreatic cancer tumor xenografts, similar to the approved drugs gemcitabine and nab-paclitaxel, however, combination of the RIT with nab-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Previously, it has been shown that LMB-100 causes a dose-dependent decrease in KLM1 new protein synthesis at 12 h with the maximal effect seen by 18 h post-initiation of treatment when using a 100 ng/mL dose. Even 24 h after washing away LMB-100, restoration of new protein synthesis is not observed [ 12 ]. We hypothesized that this prolonged protein synthesis inhibition (PSI) would lower total protein levels in cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been shown that LMB-100 causes a dose-dependent decrease in KLM1 new protein synthesis at 12 h with the maximal effect seen by 18 h post-initiation of treatment when using a 100 ng/mL dose. Even 24 h after washing away LMB-100, restoration of new protein synthesis is not observed [ 12 ]. We hypothesized that this prolonged protein synthesis inhibition (PSI) would lower total protein levels in cells.…”
Section: Resultsmentioning
confidence: 99%
“…Since EF-2 is a non-redundant enzyme critical for protein translation, PE activity halts new protein synthesis in target cells [ 11 ]. This is a lethal insult in many cell types, including some PDACs [ 6 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mesothelin-targeting rITs are enhanced by various small molecules [ 25 27 ] or the chemotherapeutic drug paclitaxel [ 28 30 ]. Paclitaxel enhances the efficacy of bolus doses of mesothelin-targeted rIT in vivo [ 28 , 29 , 31 ], which was translated in a new clinical trial testing the combination (NCT02810418).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data confirm the hypothesis that new immunotoxins actually investigated in clinical trials, such as LMB-100 (previously named RG7787), might have synergistic anticancer effects when used in combination with taxanes or other standard chemotherapy. 39 …”
Section: Msln As a Therapeutic Target In Other Solid Tumorsmentioning
confidence: 99%